Focal But Not Diffuse Myocardial Fibrosis Burden Quantification Using Cardiac Magnetic Resonance Imaging Predicts Left Ventricular Reverse Modeling Following Cardiac Resynchronization Therapy. (17th December 2015) - CHEN, ZHONG; SOHAL, MANAV; SAMMUT, EVA; CHILD, NICK; JACKSON, TOM; CLARIDGE, SIMON; COOKLIN, MICHAEL; O'NEILL, MARK; WRIGHT, MATTHEW; GILL, JASWINDER; CHIRIBIRI, AMEDEO; SCHAEFFTER, TOBIAS; et al.
Focal But Not Diffuse Fibrosis Burden Predicts CRT Remodeling Response: Introduction: Many heart failure patients with dyssynchrony do not reverse remodel (RR) in response to cardiac resynchronization therapy (CRT). The presence of focal and diffuse interstitial myocardial fibrosis may explain this high nonresponse rate. T1 mapping is a new cardiac magnetic resonance imaging (CMR) technique that overcomes the limitations of conventional contrast CMR and provides reliable quantitative assessment of diffuse myocardial fibrosis. The study tested the hypothesis that focal and diffuse fibrosis quantification would correlate with a lack of left ventricular (LV) RR to CRT. Methods and Results: In a prospective study of 48 consecutive patients (27 ischemic cardiomyopathy, 21 dilated cardiomyopathy) LV scar burdens were quantified (scar core and gray zone using late gadolinium enhancement LGE CMR; interstitial fibrosis using T1 mapping) before CRT implant. LV RR was defined by a ≥ 15% reduction in LV end‐systolic volume 6 months postimplant. Twenty‐seven (56%) patients were responders with RR. Association between scar quantification and LV RR was assessed using the Poisson regression model. Univariate analysis showed that QRS duration/morphology, scar core, and gray zone volumes expressed as % of LV mass and extracellular volume index (ECV) (a measure of interstitial fibrosis from T1 mapping) to be significant predictors of LV RR. Multivariable‐adjusted analyses demonstrated scar core quantification (≥13.7% LV mass) to be the only independent predictor of LV RR (prevalence ratio 0.40, P = 0.038). Conclusions: Focal scar burden detected by LGE CMR is associated with a poor response to CRT. Diffuse interstitial fibrosis assessment by T1 mapping, however, is not independently predictive of CRT response.